PKCδ serves as a potential biomarker and therapeutic target for microglia‐mediated neuroinflammation in Alzheimer's disease - Du, Ying; Guo, Tiantian; Hao, Yunfeng; Li, Chuan; Tang, Linghui; Li, Xia; Zhang, Xiaoxiao; Li, Lin; Yao, Dan; Xu, Xia; Si, Huaxing; Zhang, Jinghan; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION To investigate the role of a novel type of protein kinase C delta (PKCδ) in the neuroinflammation of Alzheimer's disease (AD). METHODS We analyzed PKCδ and inflammatory cytokines levels in cerebrospinal fluid (CSF) of AD and normal controls, as well as their correlations. The cellular expression pattern of PKCδ and the effects of PKCδ modulation on microglia‐mediated neuroinflammation were evaluated by quantitative real‐time polymerase chain reaction (qRT‐PCR), western blot, RNA sequencing (RNA‐seq), and immunofluorescence staining. RESULTS PKCδ levels were increased dramatically in the CSF of AD patients and positively correlated with cytokines. PKCδ is expressed mainly in microglia in the brain. Amyloid beta (Aβ) stimulation increased PKCδ expression and secretion, which led to upregulation of the nuclear factor kappa B (NF‐κB) pathway and overproduction of proinflammatory cytokines. Downregulation or inhibition of PKCδ attenuated Aβ‐induced microglial responses and improved cognitive function in an AD mouse model. DISCUSSION Our study identifies PKCδ as a potential biomarker and therapeutic target for microglia‐mediated neuroinflammation in AD. Highlights Protein kinase C delta (PKCδ) levels increase in cerebrospinal fluid (CSF) of patients with Alzheimer's disease (AD), and positively correlate with elevated inflammatory cytokines in human subjects. PKCδ is expressed mainly in microglia in vivo, whereas amyloid beta (Aβ) stimulation increases PKCδ expression and secretion, causing upregulation of the nuclear factor kappa B (NF‐κB) pathway and production of inflammatory cytokines. Downregulation or inhibition of PKCδ attenuates Aβ‐enhanced NF‐κB signaling and cytokine production in microglia and improves cognitive function in AD mice. PKCδ serves as a potential biomarker and therapeutic target for microglia‐mediated neuroinflammation in AD.